Sources and characteristics of terrestrial carbon in Holocene-scale sediments of the East Siberian Sea - K. Keskitalo; T. Tesi; T. Tesi; T. Tesi; L. Bröder; L. Bröder; A. Andersson; A. Andersson; C. Pearce; C. Pearce; M. Sköld; I. P. Semiletov; et al. (Climate of the Past, 2017)
Thawing of permafrost carbon (PF-C) due to climate warming can remobilise considerable amounts of terrestrial carbon from its long-term storage to the marine environment. PF-C can be then be buried in sediments or remineralised to CO2 with implications for the carbon–climate feedback. Studying historical sediment records during past natural climate changes can help us to understand the response of permafrost to current climate warming. In this study, two sediment cores collected from the East Siberian Sea were used to study terrestrial organic carbon sources, composition and degradation during the past  ∼ 9500 cal yrs BP. CuO-derived lignin and cutin products (i.e., compounds solely biosynthesised in terrestrial plants) combined with δ13C suggest that there was a higher input of terrestrial organic carbon to the East Siberian Sea between ∼ 9500 and 8200 cal yrs BP than in all later periods. This high input was likely caused by marine transgression and permafrost destabilisation in the early Holocene climatic optimum. Based on source apportionment modelling using dual-carbon isotope (Δ14C, δ13C) data, coastal erosion releasing old Pleistocene permafrost carbon was identified as a significant source of organic matter translocated to the East Siberian Sea during the Holocene.